Pandangan Penghulu Kantor Urusan Agama (KUA) Kecamatan Pangkalan Susu Kabupaten Langkat Tentang Wali Nikah Berhalangan Hadir Taukil Wali Menggunakan Media Digital - Asfanrudin Lingga; As’ad Badar; Syahrul Affan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study examines the views of the penghulu at the KUA of Pangkalan Susu Subdistrict regarding the use of digital media for proxy marriage (taukil wali) when the guardian of the bride is unable to attend. The interview results show that the use of digital media is considered valid as long as it meets the requirements of Islamic law and applicable regulations, such as the verification of the guardian's identity, clear consent through digital communication, and the presence of valid witnesses. Despite technical challenges and public doubts, the KUA ensures that procedures are carried out according to sharia law. Overall, digital proxy marriage at KUA Pangkalan Susu is accepted as a valid solution in marriage practices.